Kemampuan Menulis Karya Ilmiah - Anah, Anah; Repelita, Tridays; Sulaeman, Dita Natasya; Ramadhan, Lexa (Peneliti.net, 2025)
The needs related to students' ability to write academic journals are more than just completing lectures and papers and completing research. However, students' ability to write academic journals influences whether or not they meet higher education quality standards. We also consider that students have a very large role in meeting education quality standards. The aim of writing is to increase students' skills in writing academic journals. Observation results show that students can improve their understanding and skills when writing academic papers. In addition, students can independently publish papers in prestigious scientific journals. To meet university quality standards, students' roles are expected to contribute to research productivity, community service and publications.